Entrepreneurial Factors Influencing Business Success in Micro, Small and Medium Enterprises in Muaradua Subdistrict South Oku Regency: ENTREPRENEUR - Dyah Ayu Putriani; Gultom, Angga (Journal of Islamic Economics Perspectives, 2020)
Abstract Analyzer used in this research is multiple linear regression. This study discusses the influence of the business environment, the availability of capital and marketing strategies that influence the success of Micro, Small and Medium Enterprises (UMKM) in Muaradua subdistrict South OKU Regency either simultaneously or partially. The results of this study were found positive and significant influence both partially and simultaneously between the Business Environment (X1), availability of capital (X2) and Strategic Marketing (X3) influence the entrepreneurial success (Y). R² value (Adjusted R Square) of 0.920 or (92%). This shows that the Business Environment (X1), Capital Availability (X2) and Strategic Marketing (X3) influence the entrepreneurial success (Y) while the remaining 8% are influenced or explained by other variables not included in the model of this study is the participation of members, cooperative management, cooperative management and cooperative financial report (Hanafiah, 2012). Keywords: business environment, availability of capital, marketing strategy